2008
DOI: 10.1111/j.1365-2982.2007.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroactive steroids and fatigue severity in patients with primary biliary cirrhosis and hepatitis C

Abstract: Fatigue is one of the most common non-specific symptoms associated with several disease states including liver diseases. Recently, it was reported that levels of progesterone metabolites such as allopregnanolone (3alpha,5alpha-tetrahydroprogesterone; 3alpha,5alpha-THP) and isopregnanolone (3beta,5alpha-THP) were increased in plasma of patients with chronic fatigue syndrome. We hypothesize that THP metabolites might be associated with fatigue commonly observed in chronic liver diseases. We evaluated fatigue sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Sickness behaviour in BDL mice was enhanced by depletion of Treg and diminished following Treg infusion. This interpretation is in accordance with data from PBC patients, in whom an increased plasma concentration of neurosteroids, which activate the GABA-A receptor and result in neuroinhibition, has been found [7]. No remarkable changes were found in TNFa or IL-1b levels.…”
supporting
confidence: 92%
“…Sickness behaviour in BDL mice was enhanced by depletion of Treg and diminished following Treg infusion. This interpretation is in accordance with data from PBC patients, in whom an increased plasma concentration of neurosteroids, which activate the GABA-A receptor and result in neuroinhibition, has been found [7]. No remarkable changes were found in TNFa or IL-1b levels.…”
supporting
confidence: 92%
“…Some of progesterone metabolites are positive allosteric modulators of the gamma-aminobutyric acid type A (GABA-A) receptor and readily cross the blood-brain barrier. It might be that increased inhibition through GABA-A receptors due to the accumulation of neuroinhibitory steroids may represent an important pathophysiological mechanism of fatigue in chronic liver diseases [14].…”
Section: Discussionmentioning
confidence: 99%
“…Each item uses a 5-grade scale with higher scores denoting increased fatigue. Fatigue Impact Scale was applied in many studies regarding fatigue in PBC patients [1,10,[14][15][16][17][18][19][20][21][22][23].…”
Section: Fatigue Impact Scalementioning
confidence: 99%
“…48,49 progesterone metabolites a study has reported that levels of progesterone metabolites, such as allopregnanolone (also known as 3α, 5αtetrahydroprogestrone [3α, 5αtHP]) and iso pregnanolone (also known as 3α, 5βtHP) are increased in the plasma of patients with PBC. 50 the increased levels of these neuroinhibitory steroids may have a role in sleep disturbance and fatigue in patients with chronic liver disease. 18 intramuscular administration of progester one, which produces an increase in the plasma level of 3α, 5αtHP, to healthy individuals was shown to induce sedativelike effects and a feeling of fatigue in men and women.…”
Section: Pathogenesis Of Fatiguementioning
confidence: 98%